Acupuncture for treating tic disorders in children: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Fu, Qianfang; Zhang, Xilian; Yan, Haihong; Xu, Jiabao; Liu, Hui; Yang, Libin; Zhao, Shuyi; Rong, Ping; Ma, Rong
Abstract: Background: Tic disorders (TDs) are a group of neurodevelopmental disorders in children, while pharmacotherapy is often associated with various side effects and has limited clinical effects for some patients, thus significantly affecting patients' quality of life. Studies have found acupuncture shows certain advantages in the treatment of TDs. However, there is no high level of evidence evaluating the effectiveness and safety of acupuncture for children with TDs. Methods: Each data of acupuncture for treating TDs will be searched. We will search for related English and Chinese databases. The time is limited from inception until November 2020. The primary outcome is the reduction rate (amount) of tic severity using related scales or methods, and the secondary outcomes include recurrence rate and adverse events. The risk of bias will be assessed, and the RevMan5.3 and Stata14.0 will be performed for meta-analysis. Finally, we will assess the level of the resulting evidence. Results: The results of the study will synthesize the current evidence and be published in peer-reviewed journals. Conclusions: This research aims to provide convincing evidence of the effectiveness and safety of acupuncture for treating TDs in children. INPLASY registration number: INPLASY2020110050.